Association of social isolation, loneliness and genetic risk with incidence of dementia: UK Biobank Cohort Study. Issue 2 (23rd February 2022) - Elovainio, Marko; Lahti, Jari; Pirinen, Matti; Pulkki-Råback, Laura; Malmberg, Anni; Lipsanen, Jari; Virtanen, Marianna; Kivimäki, Mika; Hakulinen, Christian
Abstract : Background: Social isolation and loneliness have been associated with increased risk of dementia, but it is not known whether this risk is modified or confounded by genetic risk of dementia. Methods: We used the prospective UK Biobank study with 155 070 participants (mean age 64.1 years), including self-reported social isolation and loneliness. Genetic risk was indicated using the polygenic risk score for Alzheimer's disease and the incident dementia ascertained using electronic health records. Results: Overall, 8.6% of participants reported that they were socially isolated and 5.5% were lonely. During a mean follow-up of 8.8 years (1.36 million person years), 1444 (0.9% of the total sample) were diagnosed with dementia. Social isolation, but not loneliness, was associated with increased risk of dementia (HR 1.62, 95% CI 1.38 to 1.90). There were no interaction effects between genetic risk and social isolation or between genetic risk and loneliness predicting incident dementia. Of the participants who were socially isolated and had high genetic risk, 4.4% (95% CI 3.4% to 5.5%) were estimated to developed dementia compared with 2.9% (95% CI 2.6% to 3.2%) of those who were not socially isolated but had high genetic risk. Comparable differences were also in those with intermediate and low genetic risk levels. Conclusions: Socially isolated individuals are at increased risk of dementia at all levels of genetic risk.